The salience of the self: Self‐referential processing and internalizing problems in children and adolescents with autism spectrum disorder. Issue 5 (20th November 2016) - Burrows, Catherine A.; Usher, Lauren V.; Mundy, Peter C.; Henderson, Heather A.
Abstract : Children and adolescents with autism spectrum disorder (ASD) demonstrate atypical processing of, and memory for, self‐referenced information, which may contribute to the heightened rates of co‐occurring internalizing problems. We assessed affective and cognitive aspects of self‐referential processing in verbally‐fluent children with ASD ( N  = 79), and an age‐matched comparison sample (COM, N  = 73) of children without an autism diagnosis. We examined group differences in these two aspects of the self‐system, and their joint contributions to individual differnces in internalizing problems. Using a self‐referenced memory (SRM) task, participants indicated whether a series of positive and negative trait adjectives described themselves and a well‐known fictional character. Participants were then surprised with a recognition memory test on the same adjectives. Overall, individuals with ASD showed a reduction in the extent to which they preferentially endorsed positive over negative trait adjectives about themselves, and a reduction in their preferential memory for self‐ over other‐referenced information. Across the full sample, these two aspects of self‐referential processing jointly predicted self‐reported internalizing problems. Specifically, self‐evaluations were strongly and inversely associated with internalizing problems but only for children with relatively high SRM. These findings suggest that the salience of the self influences the extent to which affective self‐evaluations impact emotional functioning for youth both with and without ASD. Implications for basic (e.g., developmental) and translational (e.g., intervention) research are discussed. Autism Res 2017, 10: 949–960 . © 2016 International Society for Autism Research, Wiley Periodicals, Inc.